Application of homotopy-perturbation method to Klein–Gordon and sine-Gordon equations - Chowdhury, Md. Sazzad Hossien; Hashim, Ishak (Elsevier, Inc., 2009)
In this paper, the homotopy-perturbation method (HPM) is employed to obtain approximate analytical solutions of the Klein–Gordon and sine-Gordon equations. An efficient way of choosing the initial approximation is presented. Comparisons with the exact solutions, the solutions obtained by the Adomian decomposition method (ADM) and the variational iteration method (VIM) show the potential of HPM in solving nonlinear partial differential equations.